1996
DOI: 10.1111/j.1365-2672.1996.tb03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of microbiological quality and shelf‐life of catfish (Clarias gariepinus) by chemical preservatives and smoking

Abstract: Fresh catfish (Clarias gariepinus) were subjected to different concentrations of sodium benzoate or potasium sorbate and smoked traditionally before evaluation for microbiological, chemical and organoleptic characteristics during ambient tropical storage. Unsmoked fish samples showed diverse microflora (Enterobacter, Escherichia, Serratia, Bacillus, Staphylococcus, Streptococcus, Penicillium, Aspergillus and Achlya genera) while smoked samples were dominated by Gram-positive bacterial flora (Bacillus, Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
3
13
0
Order By: Relevance
“…This result demonstrated that PS was more effective against the propagating microfl ora during storage. PS provides the best bacterial inhibition of microbial growth in smoked trout fi llets during refrigerated storage, as observed by others (EFIUVWEVWERE & AJIBOYE, 1996;OMOJOWO et al, 2009). The most important feature that emphasizes the use of sorbate as a preservative is the continuous antimicrobial effect of this agent at neutral pH values (LÜCK, 1990).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This result demonstrated that PS was more effective against the propagating microfl ora during storage. PS provides the best bacterial inhibition of microbial growth in smoked trout fi llets during refrigerated storage, as observed by others (EFIUVWEVWERE & AJIBOYE, 1996;OMOJOWO et al, 2009). The most important feature that emphasizes the use of sorbate as a preservative is the continuous antimicrobial effect of this agent at neutral pH values (LÜCK, 1990).…”
Section: Resultssupporting
confidence: 57%
“…In order to diminish safety risks and prevent economic losses, using safe preservatives in fi shery products has been recommended. In the preparation of smoked catfi sh, carp, and salmon, different concentrations of PS and SL have been used as preservatives (EFIUVWEVWERE & AJIBOYE, 1996;NYKÄNEN et al, 2000;ÖKSÜZTEPE & GÜREL-INANLI, 2007;DA SILVA et al, 2008;OMOJOWO et al, 2009). In most preservative-based strategies, the effi cient inhibition of microorganisms has been achieved at 3% concentrations of PS, SL, or sodium metabisulfi te (DA SILVA et al, 2008;OMOJOWO et al, 2009), which has been also accepted as GRAS status by Food and Drug Administration (FDA).…”
mentioning
confidence: 99%
“…Smoking usually extends the shelf life of fish due to the combination effects of (i) salting, which lowers water activity resulting in reduced microbial growth, (ii) elevated temperature drying, which provides a physical surface barrier to the passage of microorganisms, and (iii) deposition of antimicrobial and antioxidant compounds, such as aldehydes, carboxylic acid and phenols, which delays microbial growth and rancidity development (Efiuvwevwere and Ajiboye, 1996;Leroi and Joffraud, 2000). Moreover, fish muscle exposed to smoke in combination with a high temperature can effectively limit harmful enzymatic reactions (FAO, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Various food preservation techniques have been utilized to improve the microbial safety and extend the shelf life of seafoods in general, including freezing, chemical preservation, salting, and smoking (Jay 1998;Nickelson et al 2001;Wood 1981). Smoking usually extends shelf life of fish due to the reduced moisture content and the effects of imparted phenolic compounds (Efiuvwevwere and Ajiboye 1996). Another shelf life promoting strategy involves salting with NaCl or with chemical preservatives.…”
Section: Introductionmentioning
confidence: 99%